Peculiarities of milk microflora of Saanen goats in the conditions of the Steppe zone of Ukraine - Bilan, M. V.; Chumak, V. O.; Chumak, S. V.; Plys, V. M.; Shkadovska, Y. D. (Regulatory Mechanisms in Biosystems, 2024)
The quality of goat milk can be affected by mesophilic aerobic and facultatively anaerobic microorganisms (MAFAnM), intestinal bacteria, psychrotrophic, some pathogenic microorganisms, fungi, etc. Traditional microbiological methods, which are used to determine the safety of milk, do not provide an opportunity to obtain an instant result, require the preparation of nutrient media and glassware, which takes up work time and is energy-consuming. We have carried out studies of goat milk by classical (using conventional and selective nutrient media) and alternative modern (using test plates, which are widely used to control microbiological contamination in the food industry) methods. As a result of the conducted research, it was established that the bacterial contamination of goat milk was within the permissible limits. There were no significant differences in the results of using the test plates. According to the classical method, the average indicators of the number of mesophilic aerobic and facultatively anaerobic microorganisms were 4.97 ± 0.14 lg CFU/mL, according to the alternative method – 4.86 ± 0.13 lg CFU/mL. Escherichia coli was isolated in four samples (with an average concentration of microorganisms of 1.86 ± 0.62 lg CFU/mL), in the same samples Enterobacter spp. in the amount of 1.77 ± 0.61 lg CFU/mL. In three samples, the presence of Proteus spp. with average concentration values of 2.19 ± 0.15 lg CFU/mL. Using an alternative method, contamination of milk with Escherichia coli (1.53 ± 0.33 lg CFU/mL) was detected in five samples, coliform bacteria were isolated in four samples (1.49 ± 0.50 lg CFU/mL). Staphylococcus aureus was not detected by any of the methods, but other representatives of the genus Staphylococcus were detected in all samples by both classical and alternative methods (2.48 ± 0.05 and 3.01 ± 0.07 lg CFU/mL). Using the classic method, it was established that two samples were positive for Enterococcus spp. (2.46 ± 0.08 lg CFU/mL), Bacillus spp. were isolated in six samples (1.70 ± 0.09 lg CFU/mL), in three – Clostridium spp. (1.66 ± 0.06 lg CFU/mL), in all six samples psychrotrophic bacteria (2.09 ± 0.26 lg CFU/mL) and yeast (2.41 ± 0.24 lg CFU/mL), four of the samples contained single colonies of mold fungi of the genus Aspergillus. Pathogens Listeria monocytogenes and Salmonella spp. not found. It will be promising to study the dependence of the milk microbiome on environmental factors, as well as the influence of the milk microbiota on the course of technological processes, quality and safety indicators during the production of goat cheese or other dairy products.